A Qualitative Exploration of Power Point Utilization in Islamic Education for Fifth-Grade Students at SDN Cibungur Tasikmalaya - Yuningsih, Siti Hadiaty; Sulistya Azahra, Astrid; Kalfin (International Journal of Humanities, Law, and Politics, 2023)
Education is a conscious and planned effort so that students can develop their potential. Islamic religious education in schools aims to shape students into individuals who are faithful, devout and have noble character. In the context of Islamic Religious Education learning, creating an interesting and conducive learning atmosphere is the teacher's main concern. Learning media such as Power Point is considered important for increasing interaction between teachers and students, although varying the use of media remains the key to avoiding student boredom. This research aims to determine the use of Power Point media in learning Islamic Religious Education (PAI) in class V at SDN Cibungur Tasikmalaya. The research method used is qualitative with data collection through interviews, observation and document analysis. Islamic Religious Education Teachers have tried to apply Power Point media to increase the interactivity and effectiveness of learning. However, this assistance also identifies obstacles related to the availability of support. The research results show that the use of Power Point media can improve the quality of Islamic Religious Education learning. However, further attention is needed to teachers' understanding and readiness in designing and implementing this media so that it can provide maximum positive impact on Islamic Religious Education learning at the fifth grade level.